2004
DOI: 10.1074/jbc.m405454200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Orientation of Pardaxin Determined by NMR Experiments in Model Membranes

Abstract: Pardaxins are a class of ichthyotoxic peptides isolated from fish mucous glands. Pardaxins physically interact with cell membranes by forming pores or voltage-gated ion channels that disrupt cellular functions. Here we report the high-resolution structure of synthetic pardaxin Pa4 in sodium dodecylphosphocholine micelles, as determined by 1 H solution NMR spectroscopy. The peptide adopts a bend-helix-bend-helix motif with an angle between the two structure helices of 122 ؎ 9°, making this structure substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
152
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(166 citation statements)
references
References 55 publications
14
152
0
Order By: Relevance
“…The boundaries of structural biology have expanded with the application of solution NMR to determine the structures of small membrane-bound peptides as well as large, multidomain membrane proteins (33)(34)(35)(36)(37)(38)(39). Here, we report the functional interaction between two membrane proteins probed by solution NMR in detergent micelles.…”
Section: Discussionmentioning
confidence: 97%
“…The boundaries of structural biology have expanded with the application of solution NMR to determine the structures of small membrane-bound peptides as well as large, multidomain membrane proteins (33)(34)(35)(36)(37)(38)(39). Here, we report the functional interaction between two membrane proteins probed by solution NMR in detergent micelles.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, this type of supramolecular polypeptide-lipid assemblies can exhibit many different morphologies that are best described by phase diagrams (3,39) where lysis, wormhole-(40) and carpet-model (41), or regions where the bilayer is unaffected or even stabilized, correspond to different regions in the diagram. The ''phase boundaries'' depend on lipid composition, temperature, salt, pH, and other environmental parameters, and thereby reflect the variable environments encountered by the peptides when interacting with the membranes of different species (39,42).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Ramamoorthy et al used specific membrane model systems and nuclear magnetic resonance (NMR) to characterize structure and dynamics of several AMPs such as pardaxins [36][37][38], MSI-78 (Pexiganan) and MSI-594 synthetic magainin analogues [39,40], MSI-843 lipopeptide [41], granulysin [42], tachyplesin [43] and a cyclic peptide subtilosin A [44]. In particular, the studies on pardaxin [36,38] have shown the role of cholesterol on inhibiting the membrane disruption and the role of the peptide on the formation of cholesterol-rich domains.…”
mentioning
confidence: 99%